Ubiquitous hub for digital natives - Rosli, Mohd Shafie; Saleh, Nor Shela; Aris, Baharuddin; Ahmad, Maizah Hura; Md. Salleh, Shaharuddin (Kassel University Press, 2016)
This study was conducted to construct a model on ubiquitous hub for digital natives. Respondents were 250 digital native generation students, from a higher learning institution in Malaysia. The result of the regression, structural equation model and path analysis revealed that multitask as well as gratification and reward nurture digital natives to learn in ubiquitous computing environment. Digital natives characteristics of reliant on graphic for communication, and attitude toward technology are rejected from the model based on the statistical evidence. Test of the relationship between multitask toward gratification and reward via structural equation model shows that both influence each other. Conclusion on the set-up of ubiquitous hub for digital natives based on the model derived are discussed.